2018
DOI: 10.4081/ija.2018.1046
|View full text |Cite
|
Sign up to set email alerts
|

Effect of salinity on Echinochloa crus-galli germination as affected by herbicide resistance

Abstract: Salinity is one of the major abiotic stresses that may affect yield and quality of crops. Salinization, in combination with the presence of aggressive weeds, such as barnyard grass (Echinochloa spp.), can be considered one of the factors responsible for reducing yield in rice fields. The aims of the study were to evaluate the salt effect on germination and first seedling growth of six different Italian common barnyard grass (E. crus-galli) populations (three sensitive and three resistant to ALS-inhibitor herbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 26 publications
5
11
0
Order By: Relevance
“…In this study, values of between 36% and 44% were observed for the emergence of sensitive populations for the highest salt level, while percentages lower than 20% were recorded for the resistant populations. Thus, emergence seems to be affected more by salinity than germination, as observed in the germination test conducted previously on the same populations; in addition, the emergence of herbicide-resistant populations was reduced to a great extent by high salt concentrations compared with the sensitive ones, as already observed for germination in a previous study (Serra et al 2018).…”
Section: Echinochloa Crus-gallisupporting
confidence: 79%
See 3 more Smart Citations
“…In this study, values of between 36% and 44% were observed for the emergence of sensitive populations for the highest salt level, while percentages lower than 20% were recorded for the resistant populations. Thus, emergence seems to be affected more by salinity than germination, as observed in the germination test conducted previously on the same populations; in addition, the emergence of herbicide-resistant populations was reduced to a great extent by high salt concentrations compared with the sensitive ones, as already observed for germination in a previous study (Serra et al 2018).…”
Section: Echinochloa Crus-gallisupporting
confidence: 79%
“…Reductions in plant height and in the biomass of E. crus-galli for increasing salinity levels were observed in previous studies (Chauhan et al 2013;Hakim et al 2011;Serra et al 2018). A study carried out on E. crus-galli seeds, collected in environments with different degrees of salinity, showed that the seeds were able to germinate up to 1.5% NaCl, while once they emerged, they only survived about 20 d at a concentration of about 1% NaCl (Rahman and Ungar 1990).…”
Section: Echinochloa Crus-gallisupporting
confidence: 54%
See 2 more Smart Citations
“…A variable germination among weedy rice populations was found in previous studies even in non-saline conditions, and a correlation with other morphological traits (hull colouration, awn presence) has been demonstrated [4,16,52]. The variable response to salt has already been shown for other weed species, such as E. crus-galli, and it can be considered as an advantage for weeds that can easily adapt and infest rice in different environments [38,53].…”
Section: Discussionmentioning
confidence: 77%